Tinospora Maqsoodiana (menispermaceae), a New Species from Madhya Pradesh, India - Mujaffar, S.; Moinuddin, S.; Mustakim, S. (Indian Forester, 2014)
A new species Tinospora (Menispermaceae), Tinospora maqsoodiana Mujaffar, Moinuddin and Mustakim from the Khandwa district of Madhya Pradesh, India is described and illustrated.